Angiotensin-converting enzyme insertion/deletion polymorphism association with obesity and some related disorders in Egyptian females: a case-control observational study. Issue 1 (December 2016) - Motawi, Tarek; Shaker, Olfat; Shahin, Nancy; Ahmed, Nancy
Abstract Background According to the WHO report in 2015, obesity is the fifth leading cause of death worldwide, and the prevalence of Egyptian female obesity is 37.5 %. Since obesity is highly influenced by genetics, and adipose tissue renin-angiotensin system is over-activated in obesity, the effect of angiotensin-converting enzyme (ACE) insertion/deletion (I/D) polymorphism on obesity and related disorders was studied in several populations, because of its effect on ACE activity. Our objective was to study the association of ACE I/D polymorphism with obesity and certain related disorders, namely hypertension, insulin resistance and metabolic syndrome, in Egyptian females. Methods Eighty female volunteers were recruited, blood pressure and body measurements were recorded and a fasting blood sample was obtained for the quantitation of glucose, lipid profile, insulin, leptin and identification of ACE I/D polymorphs. Subjects were grouped based on hypertension and obesity states. Comparisons of continuous parameters were made with independent samplet -test between two groups. The frequencies of ACE genotypes and alleles, and the association between gene polymorphism and metabolic parameters were assessed using chi-square or Fisher's exact test. Results Genotype frequencies were in Hardy-Weinberg equilibrium for all groups. Genotype distribution did not differ significantly between controls and cases of all the studied disorders. Although DD carriers had apparently higher parameters of blood pressure, lipid profile and insulin resistance, only diastolic blood pressure was almost significant (p  = 0.057). I-carriers were significantly less susceptible to hypertension than DD carriers having normal waist/hip ratio (p  = 0.007, OR = 17.29, CI = 1.81–164.96) and normal conicity index (p  = 0.024, OR = 7.00, CI = 1.36–35.93). In DD genotype carriers, a significant association was found between insulin resistance and high body mass index (p  = 0.004, OR = 8.89, CI = 1.94–40.71), waist circumference (p  = 0.003, OR = 9.63, CI = 2.14–43.36) and waist/height ratio (p  = 0.034, OR = 6.86, CI = 1.25–37.61), although the variations in percentages between DD and I-carriers were not high enough to conclude an effect of ACE I/D on such an association. Conclusions In this sample of Egyptian females, ACE I/D polymorphism was not significantly associated with obesity nor with any of its related disorders studied. The I allele seemed protective against hypertension in subjects with normal, not high, waist/hip ratio and conicity index compared to DD genotype carriers.